Ultrasound-assisted synthesis of biodegradable graphene oxide-based hydrogel nanocomposites for highly efficient and cost-effective removal of methyl orange from aqueous media - Taktak, Fulya; Gokce, Suleyman (Elsevier, 2024)
The rapid and efficient removal of synthetic dyes from wastewater is essential protecting the ecological balance and public health. Azo dyes present in the aquatic ecosystem, such as methyl orange, pose a threat to the environment and biological life. Therefore, a novel adsorbent was developed based on 2- (N-morpholino ethyl) methacrylate/graphene oxide (MEMA@GO) for the removal of methyl orange from wastewater. The X-ray diffraction spectra of MEMA@GO nanocomposite hydrogel did not show the characteristic peak of graphene oxide, indicating a uniform distribution of graphene oxide in monolayers in the polymer matrix. The scanning electron microscopy images show that MEMA@GO nanocomposite hydrogels have a porous structure. The adsorption characteristics of the hydrogel were studied under different conditions and the highest adsorption capacity was 199.67 mg/g at pH 2, at a dosage of 2.5 g/L adsorbent, at a dye concentration of 50 mg/L and an optimum time of 510 min. The kinetic data indicate that the adsorption kinetics follow the pseudo -second order, with intraparticle diffusion being one of the rate -determining steps. The thermodynamic results show that the adsorption of MeO by MEMA@10wt%GO is spontaneous and endothermic, driven by entropy. MEMA@10wt% GO showed a high degree of biodegradability under soil conditions with a mass loss of 72 %. The high adsorption capacity after eight adsorption -desorption cycles proves the high reusability of MEMA@10wt%GO. Finally, the cost analysis based on energy consumption and reagent prices showed that MEMA@GO is a cost-effective adsorbent. All these results suggest that the nanocomposite hydrogels produced are potentially very promising for practical use.
Keywords: Biodegradable; Graphene oxide; Soil burial test; Low-cost; Cost analysis